STEREOTIP BUDAYA MUBALLIGH PONDOK PESANTREN M. NATSIR DAN JAMAAH DALAM AKTIVITAS TABLIGH DI KECEMATAN LEMBAH GUMANTI SOLOK - Mistarija Mistarija; Bukhari Bukhari (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
This article explains how the cultural stereotypes of Muballigh Boarding School M. Natsir and community congregation in the tabligh in Lembah Gumanti District of Solok Regency. There is a difference in the practice of religious teaching for missionaries and the congregation / community due to differences in thinking and viewpoints in understanding religious teaching. This has been a hindrance for missionaries in delivering Islamic teachings in the Lembah Gumanti District. The method used is field research with a qualitative-descriptive approach, while the subject of this research is Muballigh Boarding School M. Natsir and community congregations in Lembah Gumanti District, Solok Regency. Data collection tools used for observation, interviews and documentary studies. The data is processed by the data selection step, data classification and analysis which is then summarized and described. The findings of the study revealed that there are differences in religious practices for Muballigh Boarding School. Hamka is in tune with the culture and culture of the community congregations, so most of the community congregations are less sympathetic to the community and less receptive to the tabloid messages delivered. The mosque community does not want to apply what Muballigh Boarding School M. Natsir, on the other hand, the communications built by the missionaries are less effective.